The problem and technology of semantic search - Yelemesova, Салтанат (Рroblems of engineering and professional education, 2023)
Challenges and opportunities of working semantic search are considered in the paper. The article also describes the features of semantic search algorithm. The existing realization problems of semantic search engines are revealed.